Urbanizing Urban Political Ecology: A Critique of Methodological Cityism. (17th February 2014) - Angelo, Hillary; Wachsmuth, David
Abstract Urban political ecology (UPE), an offshoot of political ecology that emerged in the late 1990s, has had two major impacts on critical urban studies: it has introduced critical political ecology to urban settings, and it has provided a framework for retheorizing the city as a product of metabolic processes of socionatural transformation. However, there was another goal in early UPE programmatic statements that has largely fallen by the wayside: to mobilize a Lefebvrian theoretical framework to trouble traditional distinctions between urban/rural and society/nature by exploring urbanization as a global process. Instead of following this potentially fruitful path, UPE has become bogged down in 'methodological cityism'––an overwhelming analytical and empirical focus on the traditional city to the exclusion of other aspects of contemporary urbanization processes. Thus UPE's Lefebvrian promise, of a research program that could work across traditional disciplinary divisions and provide insights into a new era of planetary urbanization, has remained unfulfilled. In this article we trace UPE's history to show how it arrived at its present predicament, and offer some thoughts on a research agenda for a political ecology not of the city but of urbanization.